ChemInform Abstract: Periodic Mesoporous Organosilicas: From Simple to Complex Bridges; a Comprehensive Overview of Functions, Morphologies and Applications. Issue 28 (21st June 2013) - Van Der Voort, Pascal; Esquivel, Dolores; De Canck, Els; Goethals, Frederik; Van Driessche, Isabel; Romero‐Salguero, Francisco J.
Abstract Review: 328 refs.